611. Infectious Disease Management of Homeless and Non-Homeless Populations in United States Emergency Departments. (31st December 2020) - Barnes, Jessica; Segars, Larry; Wasserman, Jason; Karabon, Patrick; Taylor, Tracey A
Abstract: Background: Studies have long documented the increased emergency department usage in the United States by homeless persons compared to their housed counterparts, as well as an increased overall prevalence of infectious diseases. However, there is a gap in knowledge on the treatment that homeless persons receive for these infectious diseases within United States emergency departments compared to their housed counterparts. This study seeks to understand this potential difference in treatment, including diagnostic services tested, procedures performed, and medications prescribed. Methods: This study utilized a retrospective, cohort study design to analyze data from the 2007-2010 National Hospital Ambulatory Medical Care Survey (NHAMCS) database. Complex sample logistic regression analysis was used to compare variables, including diagnostic services, procedures, and medication classes prescribed between homeless and private residence individuals seeking emergency department treatment for infectious diseases. This provided an odds ratio to compare the two populations, which was then adjusted for confounding variables. Results: Compared to private residence individuals, homeless persons were more likely (OR: 10.99, p< 0.05, CI: 1.08-111.40) to receive sutures or staples when presenting with an infectious disease in United States emergency departments. Compared to private residence persons, homeless individuals were less likely (OR: 0.29, p< 0.05, CI: 0.10-0.87) to be provided medications or immunizations when presenting with an infectious disease in United States emergency departments, and significant differences were detected in prescribing habits of multiple medication classes. Conclusion: This study detected a significant difference in suturing/stapling and medication prescribing patterns for homeless persons with an infectious disease in United States emergency departments, compared to their housed counterparts. These results provide a platform for continual research. Disclosures: All Authors : No reported disclosures